2017
DOI: 10.3389/fpls.2017.00422
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ALA1 and ALA2 Mediate RNAi-Based Antiviral Immunity

Abstract: RNA intereferencing (RNAi) pathway regulates antiviral immunity and mediates plant growth and development. Despite considerable research efforts, a few components in RNAi pathway have been revealed, including ARGONAUTEs (AGOs), DICER-LIKEs (DCLs), RNA-dependent RNA polymerase 1 and 6 (RDR1/6), and ALTERED MERISTEM PROGRAM 1 (AMP1). In this study, we performed a forward genetic screening for enhancers of rdr6 via inoculation of CMV2aTΔ2b, a 2b-deficient Cucumber Mosaic Virus that is unable to suppress RNAi-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…EMS mutagenesis in Col-0 background was performed as described previously 47 . Briefly, about 50,000 M1 seeds of Col-0 plants were incubated with 100 mM phosphate buffer (pH 7.5) 4 °C for 12 h, followed by mutagenized with 0.6% ethyl methanesulfonate (EMS) in phosphate buffer at 25 °C for 8 h. The M1 seeds were washed with sterilized water for 20 times and were grown in soil to generate the M2 population.…”
Section: Methodsmentioning
confidence: 99%
“…EMS mutagenesis in Col-0 background was performed as described previously 47 . Briefly, about 50,000 M1 seeds of Col-0 plants were incubated with 100 mM phosphate buffer (pH 7.5) 4 °C for 12 h, followed by mutagenized with 0.6% ethyl methanesulfonate (EMS) in phosphate buffer at 25 °C for 8 h. The M1 seeds were washed with sterilized water for 20 times and were grown in soil to generate the M2 population.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, ALA1 and ALA2 are required for the biogenesis of the virus-activated siRNAs (vasi-RNAs), a recently described class of RDR1-dependent endogenous siRNAs that are induced by CMV and Turnip mosaic virus (TuMV) to target diverse host genes for silencing by a DCL4-AGO2 pathway (Cao et al, 2014). Interestingly, ALA1 has also been identified independently by screening for enhancers of rdr6 via infection with CMV-2aTD2b (Zhu et al, 2017).…”
mentioning
confidence: 99%
“…To date, our observation of a 6.5-fold reduction in ala4/5 rosette diameter (Fig. 2b) is the most severe growth defect associated with a plant flippase deficiency, in comparison to a ~1.2-fold reduction for an ala3 KO (McDowell et al, 2013), a ~2.5-fold reduction for ALA1 RNAi lines grown at 8-12°C (Gomès et al, 2000), and no significant changes reported for an ala2 KO (Zhu et al, 2017), an ala6/7 KO (McDowell et al, 2015), or an ala10 KO (Poulsen et al, 2015;Botella et al, 2016). The loss of ALA4/5 also resulted in cell size reductions across multiple cell types, including leaf epidermal cells which showed a 2.7-fold reduction in surface area (Fig.…”
Section: Ala4/5 Are Flippases That Transport Pc Sm Pe and Psmentioning
confidence: 66%